Sirolimus for Kaposiform Hemangioendothelioma and Kasabach-Merritt Phenomenon in a Neonate - Cabrera, Trevor B.; Speer, Allison L.; Greives, Matthew R.; Goff, Donna A.; Menon, Neethu M.; Reynolds, Eric W. (American Journal of Perinatology Reports, 2020)
We present a case of a neonate born with kaposiform hemangioendothelioma (KHE), complicated by Kasabach-Merritt phenomenon (KMP) and other serious conditions, who was successfully treated with sirolimus. In addition to complications from thrombocytopenia and fluid overload, during the course of therapy, our patient experienced supratherapeutic drug levels at the commonly accepted starting dose of sirolimus. Patients with KHE and KMP should be closely monitored for potential complications of both the initial disease and unexpected side effects of treatments.
Keywords: kaposiform hemangioendothelioma; Kasabach-Merritt phenomenon; sirolimus